THE CANONICAL WNT PATHWAY IN GASTRIC CARCINOMA - OLIVEIRA,Levindo Alves de (2019)
ABSTRACT Background : It is believed that the Wnt pathway is one of the most important signaling involved in gastric carcinogenesis. Aim : To analyze the protein expression of canonical and non-canonical Wnt pathways in gastric carcinoma. Method : The immunohistochemistry was performed in 72 specimens of gastric carcinomas for evaluating the expression of Wnt-5a, FZD5, GSK3β, axin, CK1, ubiquitin, cyclin D1 and c-myc. Results : There were significant differences for cytoplasm and nucleus ubiquitin for moderately and well differentiated tumors (p=0.03) and for those of the intestinal type of the Lauren classification (p=0.03). The absence of c-myc was related to Lauren’s intestinal tumors (p=0.03). Expression of CK1 in the cytoplasm was related to compromised margin (p=0.03). Expression of cyclin D1 protein was more intense in male patients (p=0.03) There was no relation of the positive or negative expression of the Wnt-5a, FZD5, GSK3 and Axin with any clinicopathological variables. Conclusion: The canonical WNT pathway is involved in gastric carcinoma.